Comparative study of toxicological assessment of yttrium oxide nano- and microparticles in Wistar rats after 28 days of repeated oral administration. (9th February 2019) - Panyala, Archana; Chinde, Srinivas; Kumari, Srinivas Indu; Rahman, Mohammad Fazlur; Mahboob, Mohammed; Kumar, Jerald Mahesh; Grover, Paramjit
Abstract: Despite their enormous advantages, nanoparticles (NPs) have elicited disquiet over their safety. Among the numerous NPs, yttrium oxide (Y2 O3 ) NPs are utilised in many applications. However, knowledge about their toxicity is limited, and it is imperative to investigate their potential adverse effects. Therefore, this study explored the effect of 28 days of repeated oral exposure of Wistar rats to 30, 120 and 480 mg/kg body weight (bw) per day of Y2 O3 NPs and microparticles (MPs). Before initiation of the study, characterisation of the particles by transmission electron microscopy, dynamic light scattering, Brunauer–Emmett–Teller and laser Doppler velocimetry was undertaken. Genotoxicity was evaluated using the comet and micronucleus (MN) assays. Biochemical markers aspartate transaminase, alanine transaminase, alkaline phosphatase, malondialdehyde, superoxide dismutase, reduced glutathione, catalase and lactate dehydrogenase in serum, liver and kidney were determined. Bioaccumulation of the particles was analysed by inductively coupled plasma optical emission spectrometry. The results of the comet and MN assays showed significant differences between the control and groups treated with 120 and 480 mg/kg bw/day Y2 O3 NPs. Significant biochemical alterations were also observed at 120 and 480 mg/kg bw/day. Haematological and histopathological changes were documented. Yttrium (Y) biodistribution was detected in liver, kidney, blood, intestine, lungs, spleen, heart and brain in a dose- and the organ-dependent manner in both the particles. Further, the highest levels of Y were found in the liver and the lowest in the brain of the treated rats. More of the Y from NPs was excreted in the urine than in the faeces. Furthermore, NP-treated rats exhibited much higher absorption and tissue accumulation. These interpretations furnish rudimentary data of the apparent genotoxicity of NPs and MPs of Y2 O3 as well as the biodistribution of Y. A no-observed adverse effect level of 30 mg/kg bw/day was found after oral exposure of rats to Y2 O3 NPs.